Complicated Growth Plate Fracture: Torn Metaphyseal Periosteum with Physeal Interposition. Issue 1 (10th December 2021) - Laloo, Frederiek; Haque, Saira; De La Hoz Polo, Marcela
Teaching point: Displacement of torn periosteum into the growth plate is an uncommon pediatric entity following trauma – which can be seen on an MRI as low signal intensity physeal interposition on all pulse sequences, and requires open surgical reduction, as it may lead to growth plate bridging and subsequent extremity length discrepancy.